Budaya Organisasi dan Dampak Organisasi terhadap Lembaga Pendidikan - Syafriani, Yuni; Ramadhani, Suci (Lembaga Yasin AlSys, 2023)
Organizational culture is the basis for designing an organization because organizational culture is an organizational identity. There are several opinions about the concept of organizational culture, the most popular opinion is that organizational culture is the basis for solving external and internal problems. It is understood that organizations are created to solve problems. Organizational culture is a unified system, values, which are adhered to and used as shared guidelines for both individuals and groups in an organization or an institution. Organizations or groups will experience development and progress, if the organizational culture in an organization and the institution can be organized and run well. In this paper, the author will describe organizational culture in educational institutions, namely about the notion of organizational culture and organizational culture in educational institutions. This is very appropriate to be the focus of an educational institution, especially in achieving the desired goals.